MAKNA KETUNTASAN DALAM BELAJAR - Hernawan, Asep Herry (MAJALAH ILMIAH PEMBELAJARAN, 2008)
The masteri learning issues are significant for students to achieve their learning outcomes, especially for students who have learning difficulties. The emergence of mastery learning as one form of educational innovation has a main purpose to improve the motivation and students' effort to achieve the mastery level sufficiently. By using the mastery leaning approach to support the implementaion of "kurikulum tingkat satuan pendidikan" (KTSP), everyone who is involved in the curriculum implementation has a responsibility to understand the mastery learning approach properly including its development history, concept and the characteristics.